TOPICAL ISSUES OF REGULATION OF THE LEGAL FRAMEWORK FOR ENSURING HUMAN RIGHTS AND FREEDOMS AT THE INTERNATIONAL LEVEL - Avdeevich Avdeev, Vadim; Vadimovna Avdeeva, Ekaterina; Vasilyevich Rozenko, Stanislav; Nikolaevich Fedulov, Igor; Vyacheslavovich Kuleshov, Igor; Gennadievna Byzova, Inga (Gênero & Direito, 2020)
The article investigates the legal basis for ensuring international security in the context of the protection of peace and humanity in globalized domestic legal systems. In the context of globalization, a wave of new nationalist ideas and moods is rising and there is a tendency for states to redistribute the spheres of economic and political influence. The principle of justice is not always dominant in making certain key decisions in interstate interaction. New directions of state development in the context of globalization make it necessary to improve the system of ensuring security of the world and humanity taking into account international legal principles. Modern public policy should be aimed at preserving the right of humankind to peace and secure coexistence on a friendly basis among cooperating states. In national legal systems, a mechanism for ensuring the security of peace and humanity that takes into account regional features is becoming a priority. Attention is focused on the state of security declared by national and international law guaranteed by the international community. The development and implementation by the international community of legal principles that should form the basis for legal regulation of the state of security is of fundamental importance. The article analyzes international legal acts aimed at strategic directions of ensuring security of peace and humanity in national legal systems. The article notes that one of the directions to ensure security of the world and humanity is to bring the norms of national law into conformity with the norms, principles and provisions of international normative legal acts of regional and universal character. The research is based on private and general scientific methods of cognition. Special attention is paid to the use of comparative legal and formal-legal methods of examining objective reality. Sociological, logical and statistical methods and means of comprehending social realities have significance. The result of the analysis was the identification of factors that determine the crime development against peace and security of humanity. Conclusions were formulated concerning the trends in the implementation of the state policy which predetermines new directions of the criminal-legal policy in the field of minimizing the process of criminalizing public relations to ensure security of the world and humanity. The priority directions of social evolutionism in the field of protecting the inviolability of the interests of the world and humanity are subject to designation. Actual questions of legislative and organizational-practical character in the field of counteraction to encroachments on peace and security of mankind are considered.